‘Grim Realities’ or ‘Light of Fancy’? Charles Dickens in the Bulgarian Classroom - Zelma Catalan (Cahiers Victoriens et Edouardiens)
Charles Dickens is a writer who has always featured in the literature textbooks for the English language secondary schools in Bulgaria. In this paper I look at the way he has been presented in them in the different periods of Bulgarian history since 1945. The investigation is motivated by the belief that his status of a world-renowned literary figure depends on the dissemination of his works in non-Anglophone countries not only through the traditional mechanisms of reception but also by his inclusion in the curriculum. My examination is placed in the context of the changing institutional protocols of the Bulgarian school and the pressures they exert on the teaching of literature. In the communist past Dickens’s texts were treated exclusively as examples of social history. During and after the transition period his value has been questioned by educational ideologies that privilege language proficiency over literary competence, as well as by the efforts to redress the gender balance in the canon of British literature. Finally, I propose a change of emphasis. A greater attention to Dickens’s relation to popular culture will allow students from non-Anglophone countries to tap into the richness and variety of his art.